PENGEMBANGAN VIDEO ANIMASI PLOTAGON MATERI FOTOSINTESIS DI KELAS IV SD SUPRIYADI 02 SEMARANG - Khakim, Ludfil; Suyoto, Suyoto; Mushafanah, Qoriati; Karsono, Karsono (FKIP, PGSD, Universitas Slamet Riyadi, 2024)
The purpose of this study was to determine the validity of the Plotagon animated educational video about photosynthesis material in Class IV SD Supriyadi 02 Semarang. The research used in development research is the ADDIE model which refers to the Robert Maribe Branch. in this stage using 5 stages of development namely analysis, design, development, implementation and evaluation. The learning media uses the Plotagon application which was developed by applying learning, especially in the photosynthesis process material. The method of collecting data in this study is using observation, interviews, and questionnaires.This validity assessment was adjusted to the overall assessment of the validity test results of this development research to produce a product in the form of a plotagon animation video on photosynthesis material with details (1) the material expert validator test obtained results suitable for use and a small revision was needed with a value of 83 (2) the material expert test obtained the results are very feasible with a value of 75 (3) the media development test for students obtains a value of 76. Based on the results of the due diligence test it is concluded that the animated video plotagon on photosynthesis material is suitable for use as learning media at SD Supriyadi 02 Semarang in a good category and can be used properlyr